Developing the Jiwa Merdeka Coaching Model through Nusantara Philosophy and Practical Sufism - Santoso, Heri; Wahyudi, Imam; Usman, Abdul Malik; Rozi, Fahrur; Ridwan, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2026)
Indonesian higher education is increasingly expected to become an impactful institution contributing not only to academic competence but also to character formation, spiritual maturity, and social transformation. This study employed a Participatory Action Research (PAR) design to develop and evaluate the Coaching Membangun Jiwa Merdeka model, grounded in the integration of Nusantara philosophy and practical Sufism. The process involved module development, expert validation, and Training of Trainer (ToT) implementation at Universitas Nahdlatul Ulama Al Ghazali Cilacap in collaboration with the Faculty of Philosophy, Universitas Gadjah Mada. Thirty-two participants — consisting of teachers, lecturers, school or madrasah leaders, and students — were purposively selected. Data were collected through participatory observation, questionnaires, interviews, participant testimonies, expert judgment, and documentation, and were analysed using descriptive quantitative analysis and qualitative thematic analysis. The findings revealed a very high level of participant acceptance, with 100% of participants perceiving the training as beneficial and 93.7% expressing readiness to become Jiwa Merdeka coaches. Qualitative findings indicated that the model strengthened philosophical reflection, spiritual awareness, emotional calmness, self-understanding, and readiness to apply the method in educational and community contexts. The principal novelty of this study lies in the formulation of the Four-Step Jurus, which systematically integrates munajat and muhasabah with Al-Fatihah, Qur'anic reflection, Asmaul Husna contemplation, and conscience-based dialogue as a culturally grounded, non-Western coaching framework. The study implies that spiritually transformative coaching can serve as a practical model for character education, teacher development, student mentoring, and community empowerment within the Kampus Berdampak agenda.